2018
DOI: 10.3390/molecules23051213
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside, an Inestimable Natural Product in Treatment of Neurological and other Disorders

Abstract: Echinacoside (ECH), a natural phenylethanoid glycoside, was first isolated from Echinacea angustifolia DC. (Compositae) sixty years ago. It was found to possess numerous pharmacologically beneficial activities for human health, especially the neuroprotective and cardiovascular effects. Although ECH showed promising potential for treatment of Parkinson’s and Alzheimer’s diseases, some important issues arose. These included the identification of active metabolites as having poor bioavailability in prototype form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 79 publications
(45 reference statements)
0
33
0
2
Order By: Relevance
“…In recent years, ECH has been extensively studied in nervous system and tumour, and it has been reported to possess a variety of pharmacological effects, such as antioxidant, anti‐inflammatory, anti‐apoptosis and anti‐tumour properties 18,19 . In nerve cells, ECH significantly enhances antioxidant capacity, reduces ROS production, improves mitochondrial membrane potential (MMP) and increases cell viability, 20 exhibits protective effects on mitochondrial function and inhibits mitochondrial oxidative stress, it protects against oxidative injury and improves memory, eventually prevents neurodegeneration 21,22 . ECH also increases the activity of SOD and play a protective role in brain tissue and retina tissue, 19,23 but the specific mechanism for its antioxidant effect is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ECH has been extensively studied in nervous system and tumour, and it has been reported to possess a variety of pharmacological effects, such as antioxidant, anti‐inflammatory, anti‐apoptosis and anti‐tumour properties 18,19 . In nerve cells, ECH significantly enhances antioxidant capacity, reduces ROS production, improves mitochondrial membrane potential (MMP) and increases cell viability, 20 exhibits protective effects on mitochondrial function and inhibits mitochondrial oxidative stress, it protects against oxidative injury and improves memory, eventually prevents neurodegeneration 21,22 . ECH also increases the activity of SOD and play a protective role in brain tissue and retina tissue, 19,23 but the specific mechanism for its antioxidant effect is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has demonstrated that ECH possesses highly beneficial effects in nervous and cardiovascular system disorders as well as bone disease and therefore was proposed as a promising candidate in the treatment of Parkinson's disease and Alzheimer's disease, atherosclerosis, and osteoporosis (Liu, Yang, Dong, Zhang, & Ma, ). Also, the antioxidant property of ECH was 9.5‐fold greater than that of Trolox, indicating that it is possible to apply ECH in the future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Alipieva et al 9 reviewed the biosynthesis and pharmacological significance of verbascoside, the most popular PhG in 2014. Liu et al 81 86 Furthermore, benzene ring plane conjugation in PhGs can be increased by the α, β-conjugated unsaturated ester structures and allow electron delocalization to inhibit free radicals. 86…”
Section: F I G U R Ementioning
confidence: 99%